2006
DOI: 10.2217/14622416.7.3.387
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in Genes Regulating the HPA Axis Associated with Empirically Delineated Classes of Unexplained Chronic Fatigue

Abstract: Chronic fatigue syndrome (CFS) is characterized by persistent or relapsing fatigue that is not alleviated by rest, causes substantial reduction in activities and is accompanied by a variety of symptoms. Its unknown etiology may reflect that CFS is heterogeneous. Latent class analyses of symptoms and physiological systems were used to delineate subgroups within a population-based sample of fatigued and nonfatigued subjects [1] . This study examined whether genetic differences underlie the individual subgroups o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(59 citation statements)
references
References 28 publications
(37 reference statements)
3
55
0
1
Order By: Relevance
“…Physical activity is usually encouraged to improve conditions (e.g., tension, stiffness) and halt progression of physical disability in pain conditions. In fact, physical activity in chronic pain patients has been linked to improved physical and psychosocial outcomes, and physical exercise has showed positive impact on flexibility, social functioning, and quality of life [72][73][74][75][76]. Despite this, engagement in physical activity requires self-regulatory strength, which may be fatigued in chronic pain patients.…”
Section: Physical Activitymentioning
confidence: 99%
“…Physical activity is usually encouraged to improve conditions (e.g., tension, stiffness) and halt progression of physical disability in pain conditions. In fact, physical activity in chronic pain patients has been linked to improved physical and psychosocial outcomes, and physical exercise has showed positive impact on flexibility, social functioning, and quality of life [72][73][74][75][76]. Despite this, engagement in physical activity requires self-regulatory strength, which may be fatigued in chronic pain patients.…”
Section: Physical Activitymentioning
confidence: 99%
“…Relevant to this point, a recent biopsychosocial model of CFS and FM (Van Houdenhove & Egle, 2004;Van Houdenhove, Neerinckx, Onghena, Lysens, & Vertommen, 2001) offers a more comprehensive view of these illnesses based on a number of interactive etiological factors: (a) genetic/environmental interactions, as supported by recent studies in CFS reporting defects in genes associated with adaptation to stress (e.g., Smith, White, Aslakson, Vollmer-Conna, & Rajeevan, 2006) and studies in FM reporting early adversities such as sexual abuse (e.g., Van Houdenhove et al, 2001); (b) stress-producing personality styles characterized by an overactive, hyperachievement orientation, and lack of emotional openness (Anderberg, Marteinsdottir, Theorell, & Von Knorring, 2000;Egle et al, 1989;Johnson, Panaanen, Rahinatti, & Hannonen, 1997;Van Houdenhove et al, 2001;Ware, 1993); and (c) proximal triggering factors including physical or emotional trauma, lack of support, and daily hassles (Van Houdenhove & Egle, 2004).…”
Section: Theory and Intervention: An Examination Of The Literaturementioning
confidence: 99%
“…The newly updated schizophrenia gene meta-analysis revealed that TPH1 is one of the four genes positively associated with schizophrenia, showing strong epidemiological credibility (Allen et al, 2008). In contrast to TPH1, genetic studies have shown an association between TPH2 and suicidal behavior (Zill et al, 2004b;Li and He, 2006a), major depression (Zill et al, 2004c), panic disorder (Maron et al, 2007), chronic fatigue syndrome (Goertzelet et al, 2006;Smith et al, 2006) and Tourette syndrome (Mössner et al, 2007). However, no evidence has been found for a role of TPH2 in schizophrenia, despite several studies in this area (De Luca et al, 2005a;Higashi et al, 2007;Shiroiwa et al, 2010;Tee et al, 2010;Kim and Yoon, 2011;Zhang et al, 2011).…”
Section: Introductionmentioning
confidence: 99%